1985
DOI: 10.1093/infdis/152.6.1114
|View full text |Cite
|
Sign up to set email alerts
|

Changing Pattern of Resistant Shiga Bacillus (Shigella dysenteriae Type 1) and Shigella flexneri in Bangladesh

Abstract: Shigella dysenteriae type 1 (Shiga bacillus) has made a dramatic comeback in Bangladesh after 10 years when Shigella flexneri was the dominant serogroup. Whereas S. flexneri showed little increase in resistance to the commonly used antimicrobial agents--namely, trimethoprim-sulfamethoxazole (TMP-SMX) and ampicillin-over the years, S. dysenteriae type 1 underwent rapid changes with regard to sensitivity pattern during the last two years. The first TMP-SMX-resistant strain of S. dysenteriae type 1 was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 13 publications
1
36
0
2
Order By: Relevance
“…The extensive use of this drug has contributed to the emergence of resistant S. sonnei and sustained the resistant trait. 1,15,16 In addition to co-Trimoxazole and ampicillin, ongoing resistance of Shigella species to tetracycline, chloramphenicol, and most recently to fl uoroquinolones has been shown. Oral aminoglycosides and fi rst and second generation cephalosporins are clinically ineffective, despite their in vitro activity.…”
Section: 25mentioning
confidence: 99%
“…The extensive use of this drug has contributed to the emergence of resistant S. sonnei and sustained the resistant trait. 1,15,16 In addition to co-Trimoxazole and ampicillin, ongoing resistance of Shigella species to tetracycline, chloramphenicol, and most recently to fl uoroquinolones has been shown. Oral aminoglycosides and fi rst and second generation cephalosporins are clinically ineffective, despite their in vitro activity.…”
Section: 25mentioning
confidence: 99%
“…Vibrio cholerae resistant to commonly used antibiotics have been reported from Philippines [10], Thailand [ 11], Tanzania [12] and Kenya [13]. In Bangladesh several studies have demonstrated the extensive problems of multiple resistance in shigellae [14][15][16]. Some strains have been isolated that are resistant to all commonly available oral antimicrobials [17].…”
Section: Introductionmentioning
confidence: 99%
“…This now represents a major concern in many parts of the world. In Bangladesh the level of trimethoprim resistance rose from 5 % in 1979 to 83% in 1983 (Zaman et al, 1983;Shahid et al, 1985) whilst in England and Wales the level of resistance rose from 1.3% to 17% in the same period (Gross et al, 1984). Some studies on trimethoprim-resistant shigella have demonstrated the dominance of the type I dihydrofolate reductase whilst others have shown a significant proportion of strains which do not react with probes for genes encoding for either of the commonly occurring type I and type I1 enzymes (Chatkaeomorakot et al, 1987 (Barg el a!., 1989).…”
Section: Introductionmentioning
confidence: 99%